Conservative treatment versus reversed shoulder prothesis for proximal humerus fractures in the elderly: A meta-analysis of observational studies and randomised clinical trials. (1st June 2022) - Ferree, S; Beeres, F; Rompen, I; Link, B; Babst, R; van de Wall, B
Abstract: Objective: The treatment of complex proximal humerus fractures in elderly patients is not yet fully eluci-dated. Of all treatment options reverse shoulder arthroplasty (RSA) and non operative treat-ment (NOT) appear to provide the best results. Evidence to guide the choice between the two is sparse. Therefore, this review provides an overview of the available evidence on RSA versus non-operative treatment. Methods: Studies comparing RSA and NOT were included for direct comparison by systematic re-view and pooled analysis for patient rated outcome and range of motion. Additionally, indirect comparison of case-series and non-comparative studies on either treatment modalities was performed separately. Results: Comparative: Reverse shoulder arthroplasty resulted in better patient rated outcome scores and better range of motion. Pain and treatment satisfaction scores were better after RSA. Non comparative studies reported similar patient rated and range of motion scores for both RSA and after NOT. Conclusion: The functional and range of motion outcomes after RSA seem satisfactory and potentially superior to NOT in elderly patients. The complication rate is acceptably low and an overall revision rate of 5% was found. These results should however be viewed in light of distinct differences in patient characteristics between treatment groups.